ANALISIS PERANCANGAN SISTEM INFORMASI PENJUALAN BERBASIS WEB PADA PT. ANDARU ARTI AGUNG - Muhammad Rafii Deimas (2021)
Web-based sales information system is online sales, where customers can buy products without having to face the seller face to face. The information system is a very important role in business activities in a company activity. PT. Andaru Arti Agung is a company located in Bekasi that still uses conventional methods in processing transaction data for the sale of fresh meat products so that it takes longer and is considered less effective. The purpose of this research is to design a web-based sales information system at PT. Andaru Arti Agung in order to support the smooth running of sales transactions at the company. The development of this web-based sales information system is a step to increase sales and provide profits for the company because sales are not only made to the company but also online. The results of this study are implementing a web-based sales information system of PT. Andaru Arti Agung that have a display that is easy to understand so that it can make it easier for sellers to process sales transactions and also provide services to customers and make it easier for buyers to process transactions and access information that can be done anywhere.